Analysis of maximal isometric force and EMG signal in lower limb exercise. - Cleiton Silva Correa; Bruna Gonçalves Cordeiro da Silva; Cristine Lima Alberton; Eurico Nestor Wilhelm Neto; Antonio Carlos de Moraes; Claudia Silveira Lima; Ronei Silveira Pinto (Universidade Federal de Santa Catarina, 2011)
The aim of this study was to compare maximal isometric force (MIF) and the electrical activity of the vastus medialis, vastus lateralis, rectus femoris, gluteus maximus and biceps femoris long head muscles between maximal voluntary contractions (MVC) performed at different joint angles, and to identify the most suitable positions to normalize the electromyography (EMG) signals from each of these muscles when they are activated under dynamic conditions. Ten men ranging in age from 20 to 30 years, who were familiar with strength training exercise, were studied. MVC at different joint angles of the knee extensors and flexors (0°, 60°, 90°) and hip extensors (-30°, 0°, 60°) and flexors (90°, 120°) were tested. The MIF values differed significantly between the 60° knee flexion and 60° and 90° knee extension positions (p<0.01). The same was not observed for hip flexion or extension (p>0.05). Significantly higher EMG values were only observed for the rectus femoris muscle at 90° knee extension (p<0.01). No differences between muscles were found for knee flexion, hip flexion or hip extension at the joint angles tested (p>0.05). These results suggest that the 60° knee joint flexion position is the most suitable for assessment of knee extension and flexion MIF, and that all positions tested in this study are suitable for the assessment of hip flexion and extension.